THE MANAGEMENT OF AGE-RELATED MACULAR DEGENERATION (ARMD) IN AYURVEDIC PROSPECTIVE- A CRITICAL REVIEW - Munna Kumar (International Journal of Ayurveda and Pharma Research, 2015)
Age related macular degeneration a vision threatening disease is a degenerative disease affects man in fifth decade or onward. It is caused by irreversible damage of macula in old and risked patients like arteriosclerosis, smoking, Hypertension, DM etc. In fact ARMD appears to result from a combination of hereditary, environmental, and metabolic factors. The common complaints are difficulty vision in dim light, adaptation in different lighting condition, blurring or blind spot in central vision, and a straight line looks wavy etc. Macular degeneration is of two types, Dry and Wet type in which dry type is more prevalent. Although, macular degeneration is very common with age, Ayurveda advocates certain practice and drug which has proved better to get rid of macular degeneration. The drugs like Triphala, Tulsi, Spirulina, Punarnava, Shatavari having anti-oxidant and vitamin properties and yellow vegetable like carrot contain carotene are beneficial in ARMD. Drugs like Yastimadhu, Amala, Ginger, Cardamom, Rose, Curcumin etc. has been proven anti-angiogenic properties and are beneficial to prevent neo-vascular age-related macular degeneration (NVAMD). In one study found that Tarpanawith Triphala Ghrita is beneficial and in another study those with the highest dietary intake of lutein had a 57% lower risk for ARMD such as Kale, Spinach, Mustard green, Shatavari, etc.